2015
DOI: 10.1038/srep15387
|View full text |Cite
|
Sign up to set email alerts
|

Fast and intense green emission of Tb3+ in borosilicate glass modified by Cu+

Abstract: We present photoluminescence properties of Tb3+ doped borosilicate glasses modified by Cu+. Around 5-time enhanced emission at 541 nm due to the superposed emission of Tb3+ and Cu+ is observed under the deep UV excitation. Excitation spectra demonstrate a greatly increased absorption of Tb3+ ions in the deep UV region towards the Cu+ excitation band, while the shortened Cu+ emission lifetime of glasses in association with presence of Tb3+ ions implies an energy transfer process from Cu+ to Tb3+ ions. Meanwhile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The values obtained for τm from this method were 18, 14, and 17 μs for samples #1, #2, and #3, respectively. A decay time on the order of μs is potentially suitable for applications concerning static imaging, UV detection [27], and plasma display panels [28][29][30]. Importantly, these decay times are substantially shorter than those typically obtained for Tb 3+ -doped glass materials, which are on the order of ms (Table 2).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The values obtained for τm from this method were 18, 14, and 17 μs for samples #1, #2, and #3, respectively. A decay time on the order of μs is potentially suitable for applications concerning static imaging, UV detection [27], and plasma display panels [28][29][30]. Importantly, these decay times are substantially shorter than those typically obtained for Tb 3+ -doped glass materials, which are on the order of ms (Table 2).…”
Section: Resultsmentioning
confidence: 97%
“…In fact, examples of Tb 3+ -doped glasses showing 5 D 3 -originated blue emission with intensities comparable to those of the green emission are limited to glasses with low contents of Tb 3+ (typically no more than 1 mol%) [14,15,[17][18][19]. The green luminescence decay time of Tb 3+ -doped glasses is typically on the order of ms [16,[20][21][22][23][24][25][26], which normally does not satisfy the fast response time required for some applications, e.g., scintillation detectors [27] and plasma display panels [28,29]. In fact, examples of Tb 3+ -doped glasses with decay times on the order of µs are rare [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that the T g of borosilicate is in the range of 440-560 1C and that of quartz is B1200 1C, which are, respectively, lower and higher than the annealing temperature (600 1C). [55][56][57][58][59] From the photograph shown in Fig. S8 (sideview) (ESI †), it is noted that the SLG and borosilicate (Fig.…”
Section: Sensing Mechanismmentioning
confidence: 99%
“…This approach is based on the concept that scintillating nanoparticles, such as Tb 3+ -doped LaF 3 crystal (LaF 3 :Tb), can locally convert X-ray into light and the emitted luminescences are able to activate the photosensitizers on the mechanism of fluorescence resonance energy transfer (FRET), further resulting in activating photosensitizer to induce 1 O 2 for cancer therapy [8]. The conversion of X-ray into fluorescence emission by LaF 3 :Tb is based on the mechanism that Tb 3+ ions exhibit the transitions resulting mainly from the excited level, 5 D 4 , down to the lower levels, 7 F j ( j  = 6–3), and can be accompanied by the photoluminescence properties as Tb 3+ doped in low vibrational energy and high resistivity properties of LaF 3 host material [9, 10]. LaF 3 :Tb has demonstrated luminescence at 487, 542, 582, and 620 nm under the excitation of X-ray [10].…”
Section: Introductionmentioning
confidence: 99%